2005
DOI: 10.1002/app.22453
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and thermal properties of randomly branched poly(butylene isophthalate) containing sodium sulfonate groups

Abstract: ABSTRACT:Randomly branched poly(butylene isophthalate) samples containing sodium sulfonate groups were prepared from dimethyl isophthalate, 3,5-bis(carbomethoxycarbonyl) benzene sulfonate, tris(hydroxyethyl) isocyanurate, and 1,4-butanediol, according to the well-known twostage polycondensation procedure. The polymers, containing various amounts of branching units and ionic groups, demonstrated to be soluble in the most common organic solvents, an evidence that gelation was not reached under the polymerization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…Additionally, the increase in nucleation rate from PLA_0 to PLA_3 is confirmed. This last finding is in accordance with those of other articles focused on the effect of molar mass on the crystalline phase nucleation of polyesters . Chen et al thus reported that increasing the M w of PTT and poly(ε‐caprolactone) led to some denser spherulitic populations.…”
Section: Resultssupporting
confidence: 90%
“…Additionally, the increase in nucleation rate from PLA_0 to PLA_3 is confirmed. This last finding is in accordance with those of other articles focused on the effect of molar mass on the crystalline phase nucleation of polyesters . Chen et al thus reported that increasing the M w of PTT and poly(ε‐caprolactone) led to some denser spherulitic populations.…”
Section: Resultssupporting
confidence: 90%
“…Polyelectrolytes and particularly ionomers are materials of great technological interest due to the fact that the ionic groups can interact with each other disturbing the supramolecular structure and modifying their physical and mechanical properties 1–5. Several examples of random and telechelic copolyester ionomers derived from poly(ethylene terephthalate) (PET)6–10 or poly(butylene terephthalate) (PBT)11–13 have been reported, where the main changes that were observed by the insertion of the ionic groups were a reduction in crystallizability as well as an increase of the glass transition temperature. Additionally they showed an increase in the melt viscosity caused by the ionic interactions.…”
Section: Introductionmentioning
confidence: 99%